Very late stent thrombosis of bare-metal coronary stent nine years after primary percutaneous coronary intervention - Đurić Predrag; Obradović Slobodan; Stajić Zoran; Spasić Marijan; Matunović Radomir; Romanović Radoslav; Đenić Nemanja; Jović Zoran (Vojnosanitetski Pregled)
Introduction. Stent thrombosis (ST) in clinical practice can be classified according to time of onset as early (0–30 days after stent implantation), which is further divided into acute (< 24 hours) and subacute (1–30 days), late (> 30 days) and very late (> 12 months). Myocardial reinfaction due to very late ST in a patient receiving antithrombotic therapy is very rare, and potentially fatal. The procedure alone and related mechanical factors seem to be associated with acute/subacute ST. On the other hand, in-stent neoathero-sclerosis, inflammation, premature cessation of antiplatelet therapy, as well as stent fracture, stent malapposition, un-covered stent struts may play role in late/very late ST. Some findings implicate that the etiology of very late ST of bare-metal stent (BMS) is quite different from those following drug-eluting stent (DES) implantation. Case report. We presented a 56-year old male with acute inferoposterior ST segment elevation myocardial infarction (STEMI) related to very late stent thrombosis, 9 years after BMS implantation, despite antithrombotic therapy. Thrombus aspiration was successfully performed followed by percutaneous coronary intervention (PCI) with implantation of DES into the pre-viously implanted two stents to solve the in-stent restenosis. Conclusion. Very late stent thrombosis, although fortu-nately very rare, not completely understood, might cause myocardial reinfaction, but could be successfully treated with thrombus aspiration followed by primary PCI. Very late ST in the presented patient might be connected with neointimal plaque rupture, followed by thrombotic events.